Comparative Studies on Combustion Characteristics of Blended Crude Jatropha Oil with Magnetic Liquid Catalyst and DEX under Normal Gravity Condition - Nanlohy, Hendry Y. (Universitas Negeri Malang, 2021)
A comparative study on the combustion characteristics of a single droplet fueled by DEX, crude jatropha oil (CJO), and a mixture of CJO with a magnetic liquid catalyst of rhodium trisulfate has been carried out under normal gravity conditions. The high viscosity of crude jatropha oil makes it difficult to burn under normal conditions (room temperature and atmospheric pressure), therefore the addition of a magnetic liquid catalyst rhodium trisulfate is needed to improve the properties of crude jatropha oil. As a catalyst, rhodium trisulfate has the potential to improve combustion performance while improving the physical properties of crude jatropha oil as an alternative fuel for the better. Furthermore, performance tests were also carried out with DEX fuel with a cetane number (CNs) 53. The results showed that compared to DEX, it was seen that the liquid metal catalyst rhodium trisulfate succeeded in making crude jatropha oil more charged so that the combustion process was better. This is evidenced by a significant change in the dimensions of the flame and an increase in the combustion temperature. Moreover, it is also seen that the burning rate increases and the ignition delay become faster.